Geometrically bounded singularities and joint limits prevention of a three dimensional planar redundant manipulator using artificial neural networks - Yahya, S.; Moghavvemi, M.; Almurib, H.A.F. (2012)
This paper presents an Artificial Neural Network (ANN) based on the nonlinear dynamical control of a three-dimensional six degrees of freedom planar redundant manipulator. An ANN controller is used for the computation of fast inverse kinematics, and is effective on geometrically bounded singularities and joint limits prevention of redundant manipulators. The radial basis function neural network has been used to estimate the centrifugal and gravitational effects of the joints, when the end-effector follows a desired path.